Numerical investigation on the condensation of R134a, R1234ze(E) and R450A in mini-channels. (October 2021) - Liu, Yuce; Wen, Jian; Xu, Pan; Khan, Misbah; Wang, Simin; Tu, Jiyuan
Abstract: R450A is one of R134a substitutions owing to its low GWP and similar refrigeration performance. The existing researches are mostly about its performance in refrigeration systems. This paper focuses on its heat transfer characteristics in condensation. By combining the SST k-ω model with the VOF method, the condensation of R450A, and its two components, R134a and R1234ze(E), in mini-channels were explored. The mass flux ranges from 400 to 800 kgm −2 s −1 . The vapor quality is between 0.4 and 1. The tube diameters are 1mm and 2mm. The results show when the mass flux is 400, 600, and 800 kgm −2 s −1, HTC of R134a is 11.3%-16.3%, 7.5%-15.3%, and 8.2%-14.7% higher than that of R450A, and HTC of R1234ze(E) is 5.2%-12.0%, 4.9%-12.5%, and 6.7%-14.1% higher than that of R450A. Moreover, their film thickness and axial velocity are also compared. When the vapor quality is 0.5, 0.7, and 0.9, compared with the average liquid film of R450A, that of R1234ze(E) is 1.2%, 8.8%, and 11.1% thinner and that of R134a is 4.4%, 3.6%, and 1.0% thicker, respectively. The effects of vapor quality, mass flux, channel diameter, and fluid property on the condensation of R450A are also analyzed.